Numerical study on characteristics of unsteady flow in a centrifugal pump volute at partial load condition. Issue 6 (3rd August 2015) - Tan, Lei; Zhu, Baoshan; Wang, Yuchuan; CAO, Shuliang; Gui, Shaobo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to elucidate the detailed flow field and cavitation effect in the centrifugal pump volute at partial load condition. Design/methodology/approach – Unsteady flows in a centrifugal pump volute at non-cavitation and cavitation conditions are investigated by using a computation fluid dynamics framework combining the re-normalization group k-e turbulence model and the mass transport cavitation model. Findings – The flow field in pump volute is very complicated at part load condition with large pressure gradient and intensive vortex movement. Under cavitation conditions, the dominant frequency for most of the monitoring points in volute transit from the blade passing frequency to a lower frequency. Generally, the maximum amplitudes of pressure fluctuations in volute at serious cavitation condition is twice than that at non-cavitation condition because of the violent disturbances caused by cavitation shedding and explosion. Originality/value – The detailed flow field and cavitation effect in the centrifugal pump volute at partial load condition are revealed and analysed.